A clinicopathologic study of mediastinal lesions with special emphasis on thymomas - Shamsuddin, Fatima; Khadilkar, Urmila N; Saha, Debarshi; Sreedharan, Sily (International Journal of Research in Medical Sciences, 2017)
Background: Mediastinal masses are relatively uncommon lesions that sometimes pose an interesting diagnostic and therapeutic problem for the clinician. Thymomas are one of the common mediastinal neoplasms and exhibit a wide spectrum of morphologic features and an unrivalled frequency of other autoimmune diseases. The great morphologic variability and heterogeneity in thymomas has rendered their histological classification difficult and highly controversial. Methods: This retrospective and descriptive study on thymoma was done in the department of pathology, Kasturba Medical College Mangalore (Manipal University), India over a period of five years from January 2006 to June 2011. Histopathology sections taken were stained with routine Hematoxylin and Eosin stains in every case. Additional stains and immunohistochemistry were done as required. Results: Total number of mediastinal lesions studied was 66, with thymomas making up 15 cases. The age range of patients with thymomas was 22 to 65 years with a mean of 48 years. The most common histologic sub-type of thymoma was B2. Type AB thymoma was associated with bad prognosis. Five cases of thymomas were associated with Myasthenia Gravis. All thymomas showed cytokeratin positivity. Reticulin fibers were seen around individual tumor cells in Type A thymoma while Type B2 showed around tumor nests. Conclusion: Thymomas are rare & interesting neoplasm located in the mediastinum. A histomorphological analysis aided by immunohistochemistry and radiology permits an exact diagnosis and also allows for differentiation between benign and malignant neoplasms.